An approach for estimating the probability of collision between marine risers - He, J. W. (2013)
A marine riser must be designed with a high reliability as failure is disastrous. It is desirable for risers to be arranged in proximity to maximize the available subsea space. However, collision between neighboring risers is an issue that needs to be addressed. This paper presents a novel and efficient procedure for estimating the probability of riser clashing, so that the designer can optimally balance economy and risk. The proposed approach is based on post-processing the nodal positions obtained from time domain analyses, which are typically performed to satisfy other design requirements. A certain process is defined to characterize the instantaneous severity of the system response with respect to a potential collision event. The crossing rate of the process is extrapolated to the failure threshold to estimate the failure probability. Case studies, involving two flexible risers, are conducted to verify various hypotheses made in the method. Amongst other things, it is demonstrated that the extrapolation strategy is robust, and will generally result in a conservative prediction for riser clashing.